Cadmium phytoextraction through Brassica juncea L. under different consortia of plant growth-promoting bacteria from different ecological niches - Qiong Wang; Qiyao Zhou; Lukuan Huang; Shun’an Xu; Yingyi Fu; Dandi Hou; Ying Feng; Xiaoe Yang (Ecotoxicology and Environmental Safety, 2022)
Combined bioaugmentation inoculants composed of two or more plant growth-promoting bacteria (PGPB) were more effective than single inoculants for plant growth and cadmium (Cd) removal in contaminated soils. However, the principles of consortia construction still need to be discovered. Here, a pot experiment with Cd natural polluted soil was conducted and PGPB consortia with different ecological niches from hyperaccumulator Sedum alfredii Hance were used to compare their effects and mechanisms on plant growth condition, Cd phytoextraction efficiency, soil enzymatic activities, and rhizospheric bacterial community of Brassica juncea L. The results showed that both rhizospheric and endophytic PGPB consortia inoculants promoted plant growth (6.9%–22.1%), facilitated Cd uptake (230.0%−350.0%) of oilseed rape, increased Cd phytoextraction efficiency (343.0%−441.0%), and enhanced soil Cd removal rates (92.0%−144.0%). PGPB consortia inoculants also enhanced soil microbial carbon by 22.2%−50.5%, activated the activities of soil urease and sucrase by 74.7%−158.4% and 8.4%−61.3%, respectively. Simultaneously, PGPB consortia inoculants increased the relative abundance of Flavobacterium, Rhodanobacter, Kosakonia, Pseudomonas and Paraburkholderia at the genus level, which may be beneficial to plant growth promotion and bacterial phytopathogen biocontrol. Although the four PGPB consortia inoculants promoted oilseed growth, amplified Cd phytoextraction, and changed bacterial community structure in rhizosphere soil, their original ecological niches were not a decisive factor for the efficiency of PGPB consortia. therefore, the results enriched the present knowledge regarding the significant roles of PGPB consortia as bioaugmentation agents and preliminarily explored construction principles of effective bioaugmentation inoculants, which will provide insights into the microbial responses to combined inoculation in the Cd-contaminated soils.